2022
DOI: 10.1002/ptr.7456
|View full text |Cite
|
Sign up to set email alerts
|

A review: Pharmacology and pharmacokinetics of Schisandrin A

Abstract: Schisandrin A (SA) is a bioactive lignan isolated from the traditional Chinese medicine Fructus schisandrae chinensis. In recent years, it has attracted extensive attention because of its multiple pharmacological activities. This review is the first to provide an overview of SA-related pharmacological effects and pharmacokinetic characteristics.The results showed that SA had many pharmacological effects, such as anti-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 140 publications
2
15
0
Order By: Relevance
“…In addition, SA displayed a mixed‐type (noncompetitive and competitive) inhibitory activity against CYP3A in RLMs. 27 Correspondingly, our in vitro data revealed that both SA and SB caused pharmacokinetic changes of poziotinib, and SB showed a stronger inhibitory activity on poziotinib with IC 50 values of 2.55 μM for M1 and 6.97 μM for M2, which exhibited the same results in animal studies. Furthermore, we supported that SA mainly inhibited poziotinib metabolism by inhibiting the enzymatic activity of CYP2D6, whereas SB mainly by inhibiting CYP3A4 in RLMs.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, SA displayed a mixed‐type (noncompetitive and competitive) inhibitory activity against CYP3A in RLMs. 27 Correspondingly, our in vitro data revealed that both SA and SB caused pharmacokinetic changes of poziotinib, and SB showed a stronger inhibitory activity on poziotinib with IC 50 values of 2.55 μM for M1 and 6.97 μM for M2, which exhibited the same results in animal studies. Furthermore, we supported that SA mainly inhibited poziotinib metabolism by inhibiting the enzymatic activity of CYP2D6, whereas SB mainly by inhibiting CYP3A4 in RLMs.…”
Section: Discussionsupporting
confidence: 72%
“…Various studies indicate that both S. chinensis berry preparations and their bioactive individual compounds, especially lignans and polysaccharides, appear to have cardioprotective potential; however, many of these works are limited to in vitro models. Nevertheless, the available literature indicates both to have anti-inflammatory, antioxidant, and anti-obesity potential [ 11 , 52 ]. For example, more details about the pharmacology and pharmacokinetics of bioactive compounds, including schisandrin A isolated from S. chinensis berries are described by Fu et al [ 11 ] and Yang et al [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the available literature indicates both to have anti-inflammatory, antioxidant, and anti-obesity potential [ 11 , 52 ]. For example, more details about the pharmacology and pharmacokinetics of bioactive compounds, including schisandrin A isolated from S. chinensis berries are described by Fu et al [ 11 ] and Yang et al [ 52 ]. In addition, various lignans from S. chinensis berries have been found to demonstrate cardioprotective potential and these are summarized in Figure 2 , together with their mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional Chinese medicine (TCM) has unique advantages in the clinical treatment of liver injury due to its characteristics of multitarget and multiapproach ( Fu et al, 2021 ). The pharmacokinetic study of TCM is helpful to elucidate the in vivo process characteristics of the active ingredients of TCM and clarify the pharmacodynamic material basis of them ( Fu et al, 2022 ). The liver is the crucial detoxifying organ, responsible for the body’s metabolism of foreign substances, including drugs.…”
Section: Introductionmentioning
confidence: 99%